PENGARUH KUALITAS PRODUK, HARGA DAN PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI WARUNG KOPI MBAH SANGKIL SURABAYA - Utomo, Pambudi; Maduwinarti, Ayun; Pratiwi, Ni Made Ida (Universitas 17 Agustus 1945 Surabaya, 2019)
A businessman must have a strategy in running his business, in addition to the business strategy of an entrepreneur should also pay attention to the behavior of consumers to arise interest in consuming products and services marketed. It is hoped that consumers can make repurchase at a later time and recommend it to others.This research aims to determine the influence of product quality, price, and service to purchase decisions at the Mbah Sangkil Coffee Shop in Surabaya, both partially and simultaneously. The research is a quantitative approach. The population in this research is all consumers of Mbah Sangkil Coffee Shop in Surabaya. Sampling techniques use accidental sampling techniques with a total sample of 100 people. The data collection techniques using polls and documentation. The data analysis techniques used are descriptive analysis and multiple linear regression. The results showed that partially, the product quality, price and quality of service had a positive and significant influence on the decision of consumer purchase at the Mbah Sangkil Coffe Shop in Surabaya. The result of the coefficient of determination of product quality, price and service have contributed to the purchase decision of 80.4%. While the remaining 19.6% is influenced by other factors or variables outside of this study.Keywords: Product quality, Price, Service, Purchase decision